A HUMAN RIGHTS-BASED APPROACH TO POVERTY REDUCTION: THE ROLE OF THE RIGHT OF ACCESS TO MEDICINE AS AN ELEMENT OF THE RIGHT OF ACCESS TO HEALTH CARE - Zannelize Strauss; Debbie Horsten (Potchefstroom Electronic Law Journal, 2013)
The prevention and treatment of infectious diseases remain among the greatest challenges faced by today's developing countries. The World Health Organisation estimates that about one-third of the world's population lacks access to essential medicine, a fact which, according to the United Nations, directly contradicts the fundamental principle of health as a human right. According to the World Summit for Social Development, poor health and illness are factors that contribute to poverty, while the adverse effects of illness ensure that the poor become poorer. A lack of access to health care, amongst other rights, (including access to medicines as an element thereof) aggravates poverty. The most important provision in international law relating to the right to health is article 12 of the United Nations International Covenant on Economic, Social and Cultural Rights. Article 12(1) of this Covenant provides a broad formulation of the right to health in international law, while article 12(2) prescribes a non-exhaustive list of steps to be taken in pursuit of the highest attainable standard of health. Article 12(2), in particular, illustrates the role that adequate access to medication plays in the right of access to health care. The United Nations Committee on Economic, Social and Cultural Rights has explicitly included the provision of essential drugs as a component of the right to health care, thereby emphasising the causal link between the lack of access to essential medicines and the non-fulfilment of the right of access to health care. As with all socio-economic rights, the resource implications of the realisation of the right to health has the result that states cannot be expected to immediately comply with its obligations in respect thereof. Instead, article 2(1) of the International Covenant on Economic, Social and Cultural Rights and the General Comments of the Committee on Economic, Social and Cultural Rights place obligations on states to take deliberate, concrete and targeted steps towards expeditious and effective full realisation of the right to health, including access to medication. The measures taken to do so must, according to General Comment 3, embrace the concept of the minimum core obligation (the minimum core in relation to medicines being access to essential medicines, at the very least). In this article it is argued that adequate access to essential medicines, as an element of the right of access to health care, could contribute to the reduction of poverty. This is done by firstly discussing the human rights-based approach to poverty reduction, whereafter attention is turned to access to medicines as an element of the right to health, with specific focus on obligations in terms of the International Covenant on Economic, Social and Cultural Rights. Finally, the role of access to medicines in reducing poverty is considered. The article concludes that poverty constitutes an infringement on human rights and will not be eradicated without the fulfilment of human rights, including the right to health. The adequate fulfilment of peoples' rights of adequate access to essential medicines will enable them to achieve a higher level of well-being, thereby reducing the level of poverty which they experience. Both the right of access to health care and to essential medicines – a crucial component thereof – thus have a significant role to play in a state's poverty reduction strategies.